Compassion and the Characterization of the Markan Jesus - Bryant, Jonathan W., (Biblical Interpretation Series ;, 2024)
Why does the Gospel of Mark make specific and repeated reference to the compassion of Jesus in the miracle stories? This volume discusses the function that compassion has in the Markan characterization of Jesus, particularly in how the terminology employed depicts Jesus as entering the suffering of others. In doing so, it underscores how this portrayal is exceptional among the stories of miracle workers in ancient Greco-Roman and Jewish literature. In Mark, this compassion toward the suffering other is a central feature of the kingdom of God, an attribute the Markan audience is challenged to emulate.